Dispute Settlement of Diplomatic Relation Reviewed In International Law (Case Study of Spionageburning Australia on The President of Indonesia) - Muhammad Iqbal Baiquni (Activa Yuris: Jurnal Hukum, 2021)
The case of espionage or spying by Australia against Indonesia is not the first time, but there have been several attempts of espionage against Indonesia. This espionage act is an act of secretly collecting intelligence data in international relations in a country. In this paper, we discuss the wiretapping case and its resolution. This paper uses normative legal research with a qualitative approach. This paper examines the chronology of cases of tapping by Australia against Indonesia, wiretapping in human rights and international law, as well as the final settlement of tensions between Indonesia and Australia through an agreement on the Code of Conduct to normalize bilateral relations between the two countries.